(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
The Jalangi River in the Nadia District was an important waterway during the colonial period. Traders from north-west and north-east India used this river route to send goods to Calcutta. This river served as the foundation for the construction of renowned towns such as Karimpur, Krishnanagar, Maheshganj, and Swarupganj. Swarupganj was, on the one hand, a resting place for traders and travelers coming from far and wide; on the other hand, it was an ideal place for collecting logistics. It was here that the British opened toll stations to collect duties from navigators. In addition, small towns on the banks of Jalangi included Palashipara, Gowari, Garuimari, and Abhaynagar Ferry Ghat. All these places were always crowded with people. The Jalangi and Bhagirathi rivers transported a variety of goods from Nadia to Calcutta and other locations. As the Jalangi River is a good waterway, the indigo planters built indigo factories at various places in the basin of this river. The Jalangi river nourished the Dakbanglo factory in Krishnanagar, the R.C. Ganj factory, and the Alpha factory. The indigo produced here used to go to Calcutta ports through the Jalangi River. This led to the development of Nadia’s economic centre around the Jalangi River. But after the 1920s, the navigability of the Jalangi River declined due to severe economic pressures. And this happened in 1903, 17 years after the construction of a bridge over the Jalangi River at Krishnanagar. We will discuss the issues related to the Jalangi River in this article.